Characterization of Interstitial Lung Disease Associated With Anti-Ribonucleoprotein Antibodies. Issue 8 (December 2020) - Lhote, Raphael; Grenier, Philippe; Haroche, Julien; Miyara, Makoto; Boussouar, Samia; Mathian, Alexis; Pha, Micheline; Amoura, Zahir; Cohen Aubart, Fleur
Abstract : Objectives: Interstitial lung disease (ILD) is a common feature of mixed connective tissue disease. However, many patients do not meet the criteria for mixed connective tissue disease and thus may be diagnosed as interstitial pneumonia with autoimmune features. The aim of this study was to characterize ILD associated with anti-ribonucleoprotein (RNP) antibodies. Methods: Chest computed tomography scans of patients with anti-RNP antibody who were seen between January 2011 and October 2015 were reviewed. The underlying disease was classified with international criteria using clinical and serological features. Results: Among 544 patients with anti-RNP antibodies, 188 had a chest computed tomography scan, and 48 (26%) of them had radiological features of ILD. The presence of ILD was significantly associated with dyspnea, crackles, arthritis, Raynaud phenomenon, myositis, and sicca syndrome. The most frequent pattern was nonspecific interstitial pneumonia in 39 patients (81%). Among patients with ILD, 17 (35%) had a radiological pattern consisting of cysts and ground-glass attenuation not fulfilling the lymphoid interstitial pneumonia criteria. In 3 patients, cysts were related to fibrosis; in 14 patients, cysts corresponded to an original ILD pattern. Conclusions: Interstitial lung disease was found in 26% of patients with anti-RNP antibodies independently of the underlying disease. Anti-RNP–associated ILD mainly corresponds to nonspecific interstitial pneumonia or an original pattern consisting of cysts and ground-glass attenuation.